Border Crossing Russian Literature into Film - Burry, Alexander; White, Frederick (Edinburgh University Press, 2016)
Each time a border is crossed there are cultural, political and social issues to be considered. Applying the metaphor of the 'border crossing' from one temporal or spatial territory into another, this book examines the way classic Russian texts have been altered to suit new cinematic environments.In these essays, international scholars examine how political and economic circumstances - from a shifting Soviet political landscape to the perceived demands of American and European markets - have played a crucial role in dictating how filmmakers transpose their cinematic hypertext into a new environment. Rather than focus on the degree of accuracy or fidelity with which these films address their originating texts, this innovative collection explores the role of ideological, political and other cultural pressures that can affect the transformation of literary narratives into cinematic offerings.